2020
DOI: 10.1002/1348-9585.12125
|View full text |Cite
|
Sign up to set email alerts
|

Association between extremely long working hours and musculoskeletal symptoms: A nationwide survey of medical residents in South Korea

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Work length that is not ideal can increase the incidence of MSDs because the longer the worker is exposed to the risk, the greater the appearance of musculoskeletal complaints. These findings were also consistent with previous studies showing a link between long working hours and the incidence of MSDs (Lee et al, 2018;Sung et al, 2020;Amiri, 2022).…”
Section: Resultssupporting
confidence: 93%
“…Work length that is not ideal can increase the incidence of MSDs because the longer the worker is exposed to the risk, the greater the appearance of musculoskeletal complaints. These findings were also consistent with previous studies showing a link between long working hours and the incidence of MSDs (Lee et al, 2018;Sung et al, 2020;Amiri, 2022).…”
Section: Resultssupporting
confidence: 93%
“…Further cross-sectional data from a national health survey in the United States, found that those working 46 hours or more per week were more likely to report neck pain, compared with working 40 hours per week 24,25 . Extremely long working hours (on average 85.6 hours per week) among medical residents in a cross-sectional study in South Korea did also show an association with upper limb and low back pain 26 . Unfortunately, none of the mentioned studies of long working hours and pain measured sleep or insomnia symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…24,25 Extremely long working hours (on average 85.6 hours per week) among medical residents in a cross-sectional study in South Korea did also show an association with upper limb and low back pain. 26 Unfortunately, none of the mentioned studies of long working hours and pain measured sleep or insomnia symptoms. This would have improved comparison to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, comprehensive research encompassing all occupations and working hours related to LBP has been lacking. The relationship between working hours and LBP has been unequivocal in studies involving certain occupations like nurses, doctors, and those involving prolonged sitting ( 11 , 31 , 32 ). The odds ratio of 1.19 (95% CI 0.92–1.53) reported in the DAG-based model of this study was even larger, 1.51 (95% CI 1.21–1.89) in the same model (data not shown), when the definition of extremely long working hours was changed.…”
Section: Discussionmentioning
confidence: 99%